An efficient digital filtering algorithm for modeling double negative meta-material FDTD simulations - Ramadan, Omar Salameh (Academy Publisher Inc., 2009)
In this paper, an efficient digital filtering algorithm is presented for modeling open region double-negative (DNG) meta-material electromagnetic applications. The proposed algorithm is based on incorporating the Bilinear frequency approximation technique and the negative index material perfectly matched layer (NIMPML) formulations into the finite difference time domain (FDTD) scheme. This leads to a set of difference equations that are consistent with the FDTD algorithm with a minimal additional storage requirements. Numerical example carried out in two dimensional domain is included to show the validity of the proposed algorithm.
3rd Mosharaka International Conference on Communications, Signals and Coding, MIC-CSC 2009 --
Keywords: Difference equations; Finite difference time domain method; Metamaterials; Signal filtering and prediction; Time domain analysis; Approximation techniques; Digital filtering; Electromagnetic applications; FDTD simulations; Negative index material; Perfectly Matched Layer; Storage requirements; Two-dimensional domain; Approximation algorithms